Eclipse : Flexible Media Processing in a Heterogeneous Multiprocessor Template. - Rutten, Martijn (Amsterdam University Press, 2007)
Consumer multimedia systems, such as DVD recorders and digital televisions contain specialized chips that implement a large part of the functionality. Traditionally, semiconductor vendors develop a custom-tailored chip for each new product to optimize cos.